2011
DOI: 10.1042/bj20110571
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase II acts through UCP3 to suppress mitochondrial reactive oxygen species production and maintain aerobic respiration

Abstract: UCP3 (uncoupling protein-3) mitigates mitochondrial ROS (reactive oxygen species) production, but the mechanisms are poorly understood. Previous studies have also examined UCP3 effects, including decreased ROS production, during metabolic states when fatty acid oxidation is high (e.g. a fasting state). However, the role of UCP3 when carbohydrate oxidation is high (e.g. fed state) has remained largely unexplored. In the present study, we show that mitochondrial-bound HK (hexokinase) II curtails oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…77,80,82,83,[96][97][98] A series of studies have demonstrated that mitoHK-II has an ability to decrease ROS generation at mitochondria to prevent opening of the mPTP. 77,80,82,84,99 As mentioned earlier, mitoHK ensures tight coupling of glucose phosphorylation and mitochondrial ATP generation. This increases electron flow in the mitochondria and thus decreases mitochondrial membrane potential, which can reduce mitochondrial ROS emission.…”
Section: Pro-survival Effect Of Hk-iimentioning
confidence: 95%
See 2 more Smart Citations
“…77,80,82,83,[96][97][98] A series of studies have demonstrated that mitoHK-II has an ability to decrease ROS generation at mitochondria to prevent opening of the mPTP. 77,80,82,84,99 As mentioned earlier, mitoHK ensures tight coupling of glucose phosphorylation and mitochondrial ATP generation. This increases electron flow in the mitochondria and thus decreases mitochondrial membrane potential, which can reduce mitochondrial ROS emission.…”
Section: Pro-survival Effect Of Hk-iimentioning
confidence: 95%
“…This increases electron flow in the mitochondria and thus decreases mitochondrial membrane potential, which can reduce mitochondrial ROS emission. 77,99 It has also been demonstrated that mitoHK-II has a direct inhibitory effect on the mPTP. The mechanism for the protection is not known, largely because the molecular composition of mPTP is not fully identified.…”
Section: Pro-survival Effect Of Hk-iimentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to HPLC, serum was diluted 10-fold. Mitochondrial Isolation-Skeletal muscle and liver mitochondria were isolated as described previously (11,35). All buffers were supplemented with 10 mM pyruvate and 2 mM malate or 10 mM succinate and filtered prior to use.…”
Section: Organ Weights and Circulating Metabolites-wt And Grx2mentioning
confidence: 99%
“…Metabolite Analysis-TCA cycle intermediate and ATP levels were assessed by HPLC as described previously (11). Mitochondria were diluted to 0.5 mg/ml in 0.5% v/v perchloric acid solution, incubated on ice for 10 min, and the precipitate removed by centrifugation.…”
Section: -Hne-hismentioning
confidence: 99%